Trader of Secrets : Paul Madriani #12 - Martini, Steve, 1946- (New York : William Morrow, 2011)
While in Paris to find a former NASA employee whose name has been found on papers left in his nemesis's apartment, Paul Madriani stumbles upon a plot to harness the destructive forces of nature using stolen technology.
Keywords: Madriani, Paul (Fictitious character) -- Fiction; Assassins -- Fiction; Nuclear weapons -- Fiction; Madriani, Paul (Fictional character) -- Fiction; Nuclear weapons -- Fiction; Suspense fiction; Mystery fiction